2016
DOI: 10.1021/acschembio.6b00306
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of Glycogen Synthase Kinase 3 with Exquisite Kinome-Wide Selectivity and Their Functional Effects

Abstract: The mood stabilizer lithium, the first-line treatment for bipolar disorder, is hypothesized to exert its effects through direct inhibition of glycogen synthase kinase 3 (GSK3) and indirectly by increasing GSK3's inhibitory serine phosphorylation. GSK3 comprises two highly similar paralogs, GSK3α and GSK3β, which are key regulatory kinases in the canonical Wnt pathway. GSK3 stands as a nodal target within this pathway and is an attractive therapeutic target for multiple indications. Despite being an active fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 63 publications
3
51
0
Order By: Relevance
“…Although the final objective of generating more mDA cells was accomplished, improving mDA subtype specificity may require using improved GSK3i or activating Wnt/β‐catenin signalling with WNTs or mimetics. Recently, two new GSK3i with higher specificity have been described, BRD1652 and BRD0209 (Wagner et al, ). These two inhibitors have IC 50 values similar to that of CHIR99021, but their effects were more selective, with the closest off‐target inhibition (CDK3) requiring a 40 times higher concentration.…”
Section: Pharmacological Tools To Activate Wnt Signallingmentioning
confidence: 99%
“…Although the final objective of generating more mDA cells was accomplished, improving mDA subtype specificity may require using improved GSK3i or activating Wnt/β‐catenin signalling with WNTs or mimetics. Recently, two new GSK3i with higher specificity have been described, BRD1652 and BRD0209 (Wagner et al, ). These two inhibitors have IC 50 values similar to that of CHIR99021, but their effects were more selective, with the closest off‐target inhibition (CDK3) requiring a 40 times higher concentration.…”
Section: Pharmacological Tools To Activate Wnt Signallingmentioning
confidence: 99%
“…In the present study, the S values for analogs 3 – 5 were all 25 μ m . The K m value is 13 μ m , which was also obtained from another study . Given these values, the Δ G value of each compound was calculated.…”
Section: Resultsmentioning
confidence: 99%
“…We previously showed that WNT3A or CHIR could both trigger NC development from hPSC, and demonstrated that this process depends on β-CATENIN for NC formation under our low-WNT anterior NC formation conditions (Leung et al, 2016). However, at the high dose of ~10μM a few other kinases may also be inhibited by CHIR (Wagner et al, 2016). Of these, Wagner et.…”
Section: Discussionmentioning
confidence: 99%